Marx after Heidegger - Jackson, ML (RMIT University, School of Art, 2013)
In the ten years between the publication of The Savage Anomaly (1981/1991b) and Insurgencies (1992/1999), the Italian political philosopher Antonio Negri substantially defined a contemporary theory of power and the State that presents the crisis of democracy as a crisis of the absolute subject in relation to constitutionalism, that which limits democracy and absolute government. From a Spinozist thinking of power as pure immanence, Negri, in Insurgencies, develops a political philosophy around two competing notions: constituent power and constituted power where the former is thought as an incessant transformative ontology of being and the latter as the relative stasis that structures threshold conditions for transformation. In discussing such transformative ontology, Negri emphasises the temporality of constituent power as an ontology of the event, and compares directly the ontological understandings of time of Marx and of Heidegger, assaying them as diametrically opposed. While this essay begins with a critical engagement with the “absolute” of Negri’s Spinoza in order to open a space of encounter for Negri, of Marx and Heidegger, its aim is not so much to articulate a philosophical understanding of time but rather to argue for a radical engagement with Heidegger within the legacies of Spinoza and Marx.